2005
DOI: 10.1074/jbc.m500777200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Calcium Measurements in Subcellular Compartments of Plasmodium falciparum-infected Erythrocytes

Abstract: The acidic food vacuole exerts several important functions during intraerythrocytic development of the human malarial parasite Plasmodium falciparum. Hemoglobin taken up from the host erythrocyte is degraded in the food vacuole, and the heme liberated during this process is crystallized to inert hemozoin. Several antimalarial drugs target food vacuolar pathways, such as hemoglobin degradation and heme crystallization. Resistance and sensitization to some antimalarials is associated with mutations in food vacuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 50 publications
1
90
1
Order By: Relevance
“…Fluo-4 is a calcium probe that fluoresces green in the presence of Ca 2ϩ . The parasite DV is a calcium store, and Ca 2ϩ egress can be used as a proxy for DV permeabilization (9). A schematic representation of the assay work flow is shown in Fig.…”
mentioning
confidence: 99%
“…Fluo-4 is a calcium probe that fluoresces green in the presence of Ca 2ϩ . The parasite DV is a calcium store, and Ca 2ϩ egress can be used as a proxy for DV permeabilization (9). A schematic representation of the assay work flow is shown in Fig.…”
mentioning
confidence: 99%
“…Previous studies have shown that Ca 2ϩ indicator dyes accumulate in the parasite acidic food vacuole (49,50), complicating measurements of cytosolic Ca 2ϩ in the intraerythrocytic parasite. Consistent with this, in the absence of probenecid we observed no Ca 2ϩ response to photolysis of caged-IP 3 and little or no response to SERCA blockade with thapsigargin in P. falciparum-infected RBCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been used in malaria research to quantify differences in acidity in chloroquine resistant and non-resistant parasite strains with pH sensitive dyes (e.g., pHluorin in [32]) or to assess Ca 2? accumulation in the parasite food vacuole with a Ca-sensitive dye (e.g., Fura Red in [49]). The selection of the dye requires careful attention and planning, as some ''standard'' ratiometric dyes for RBCs can be phototoxic for the parasite [49].…”
Section: Ratiometric Imagingmentioning
confidence: 99%
“…accumulation in the parasite food vacuole with a Ca-sensitive dye (e.g., Fura Red in [49]). The selection of the dye requires careful attention and planning, as some ''standard'' ratiometric dyes for RBCs can be phototoxic for the parasite [49].…”
Section: Ratiometric Imagingmentioning
confidence: 99%